Epidemiological Study on Chronic Venous Disease in Belgium and Luxembourg: Prevalence, Risk Factors, and Symptomatology. Issue 4 (April 2015) - Vuylsteke, M.E.; Thomis, S.; Guillaume, G.; Modliszewski, M.L.; Weides, N.; Staelens, I.
Abstract : Objective: This epidemiological study measured the prevalence of chronic venous disease (CVD) in Belgium and Luxembourg. Possible risk factors and the symptomatology were evaluated. Material and methods: A survey was carried out in Belgium and Luxembourg between May and September 2013. Patient recruitment was carried out by 406 general practitioners (GPs). Each GP screened 10–20 consecutive patients older than 18 years, and in total 6009 patients were included. Patient characteristics, prevalence of risk factors, symptomatology, and C-classification were noted. The GPs diagnosed CVD and measured the need for treatment. Patients with diagnosed CVD completed a questionnaire about their history of leg problems and a quality of life score (CIVIQ-14). These data were converted into a CIVIQ Global Index Score (GIS). Results: The mean age of the patients was 53.4 years, and they were predominantly female (67.5%). Among the 3889 symptomatic patients, heavy legs, pain, and sensation of leg swelling were the most common complaints. Among the included patients, 61.3% of patients were classified within C1-C6; however, only 45.9% of these patients were considered by the GPs to be suffering CVD. Treatment was offered to 49.5% of patients. Age and female gender correlate with a higher C-class ( p  < .001). Patients with a higher C-class (C3-C6) have significantly more pain, sensation of swelling and burning, night cramps, itching, and the sensation of "pins and needles" in the legs. Patients taking regular exercise and without a family history had a lower C-class. Higher BMI, age, female gender, family history, history of thrombophlebitis, and a higher C-class correlated with a lower GIS ( p  < .001). Of the patients with CVD, 10.4% had lost days of work because of their venous leg problems. Conclusion: CVD is a very common disease, which is underestimated. The prevalence increases with age, generates incapacity to work, and worsens the patients' quality of life.